2013
DOI: 10.5539/enrr.v3n3p45
|View full text |Cite
|
Sign up to set email alerts
|

Plankton Distribution and Diversity in Tropical Earthen Fish Ponds

Abstract: Our knowledge of the consumption of plankton by fish is still fragmentary. Trophic links between fish and plankton are often loose because plankton is a changing assemblage of pelagic organisms of valuable nutritional value. The objectives of the study were to determine the distribution and diversity of planktons in the fish ponds. Water samples for plankton analysis were collected monthly (January-December), along with water samples used for the determination of physico-chemical parameters in 250 ml bottles i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
1
2
1
Order By: Relevance
“…The Bacillariophyta was the second dominant division, while other divisions of phytoplankton exist in some seasons and with insignificant proportions for example Dinophyta, Crysophyta, and Euglenophyta. A Similar assemblage of algae Chlorophyta reported by Ikpi et al, (2013) in the Tropical Earthen Fish Ponds. A high abundance of Chlorophyta was found in wet weather with a moderate temperature (Suresh et al, 2011), this abundance might happen as a result of the cloudy weather and dilution due to rain (Paulette et al, 2011).…”
Section: Discussionsupporting
confidence: 60%
“…The Bacillariophyta was the second dominant division, while other divisions of phytoplankton exist in some seasons and with insignificant proportions for example Dinophyta, Crysophyta, and Euglenophyta. A Similar assemblage of algae Chlorophyta reported by Ikpi et al, (2013) in the Tropical Earthen Fish Ponds. A high abundance of Chlorophyta was found in wet weather with a moderate temperature (Suresh et al, 2011), this abundance might happen as a result of the cloudy weather and dilution due to rain (Paulette et al, 2011).…”
Section: Discussionsupporting
confidence: 60%
“…Whereas, the DO resulted from nanobubble treatment has the highest values in comparison to DO yielded from other aeration treatments, and the DO levels were also affecting the H'. In this study, recorded phytoplankton H' was observed higher than the results from Ikpi et al (2013) and Utojo and Mustafa (2016). To conclude, the nanobubble aeration treatment can be used as a solution to improve water quality and increase phytoplankton diversity and abundance in brackish water shrimp ponds.…”
Section: Discussioncontrasting
confidence: 54%
“…The shape of the bay that was enclosed and looked like a big fish pond resulted in relatively uniform characteristics. Such characteristic resulted in the domination of diatom group (Ikpi et al, 2013;Akter et al, 2015). The enclosed environment and the many fisheries activities have limited space, not fluent water circulation and the organic residues made the environment more selective for the growth of phytoplankton species.…”
Section: The Correlations Between the Environmental Characteristics Wmentioning
confidence: 99%